Abenaki materials, Frank Siebert Papers - Day, Gordon M.; Laurent, Joseph; Panadis, Theophile; Siebert, Frank T. (Frank Thomas), 1912-1998 (1884)
The Abenaki materials in the Siebert Papers are located primarily in Series III and V. Ther are descriptions of wars with the Iroquois from the 17th century, linguistic materials, and stories. Series V includes 5 research notebooks containing historical notes and some linguistics materials.